Inclusiveness Check Feature in Grammar-checking AI Systems - Cahyani, Dewi Yuri (E-Jurnal Medium; Vol 5 No 1 (2024): Jurnal Ilmu Komunikasi Vol 5 No 1 Tahun 2024, 2024)
This paper aims to conduct a theoretical review of the inclusiveness check feature in grammar-checking AI systems, such as those found in Grammarly and Microsoft Word. The examination of this inclusiveness check feature will involve the consideration of Politically Correct Language (PCL) and the theoretical debate surrounding it, and the process of semantic change. Drawing upon the author’s experience of using Grammarly as a writing assistant for her dissertation, this paper argues that such a feature should be critically addressed. It is suggested that these features effectively call out users for being politically incorrect and function as moral police for their way of expressing themselves.